[8+3]-cycloaddition of tropones with azaoxyallyl cations - Roy, Tony; Jacob, Anu; Bhattacharjee, Subrata; Biju, Akkattu T. (Chemistry-An Asian Journal, 2019)
Although azaoxyallyl cations are widely used as 1,3-dipoles for various cycloaddition reactions leading to nitrogen-containing heterocycles, their application in higher-order cycloaddition reaction remains scarce. Herein, we present the [8+3]-cycloaddition reaction of tropones with in situ generated azaoxyallyl cations allowing the one-step construction of cycloheptatriene-fused 1,4-oxazinones in moderate to good yields. This base-promoted new carbon-oxygen and carbon-nitrogen bond-forming reaction takes place under mild conditions in the absence of transition metal catalysts.
Keywords: 1; 4-oxazinones; azaoxyallyl cations; heterocycles; tropones; [8+3] cycloaddition